2018
DOI: 10.3390/molecules23092151
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Neuroprotective Effects of a Series of Pyrazolines against 6-Hydroxydopamine-Induced Oxidative Stress

Abstract: Parkinson’s disease (PD) is a chronic, progressive, and age-related neurodegenerative disorder characterized by the loss of midbrain dopaminergic neurons caused by the accumulation of free radicals and oxidative stress. Based on the neuroprotective properties of 2-pyrazoline derivatives, in the current work, 1-(phenyl/4-substituted phenyl)-3-(2-furanyl/thienyl)-5-aryl-2-pyrazolines (3a–i, 4a–i) were synthesized via the cyclization of the chalcones (1, 2) with suitable phenylhydrazine hydrochloride derivatives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Amongst these heterocyclic ring-containing scaffolds, pyrazolines as a class of electron-rich nitrogen heterocyclic compounds play an important role due to their extensive use as pharmacophore and synthon. Interestingly, 2-pyrazoline derivatives synthesized from chalcones have shown a variety of biological activities, such as antibacterial, antitumor, antifungal, anti-inflammatory, antioxidant, and antimalarial [18][19][20][21][22][23][24]. Previously it has been reported that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)-5-(multi-substituted-4-hydroxyphenyl)-2-pyrazoli nes showed significant human LDL-antioxidant activities (Figure 1) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these heterocyclic ring-containing scaffolds, pyrazolines as a class of electron-rich nitrogen heterocyclic compounds play an important role due to their extensive use as pharmacophore and synthon. Interestingly, 2-pyrazoline derivatives synthesized from chalcones have shown a variety of biological activities, such as antibacterial, antitumor, antifungal, anti-inflammatory, antioxidant, and antimalarial [18][19][20][21][22][23][24]. Previously it has been reported that 3-(3,5-di-tert-butyl-4-hydroxyphenyl)-5-(multi-substituted-4-hydroxyphenyl)-2-pyrazoli nes showed significant human LDL-antioxidant activities (Figure 1) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoline ring is a privileged structure in medicinal chemistry because of its wide spectrum of pharmacological activities. A number of pyrazoline derivatives have been reported for their antibacterial [1], antimalarial [2,3], anti-inflammatory [4], MAO inhibitory [5,6], antioxidant [7,8], neuroprotective [9], antidepressant [10] and anticancer activity [11][12][13][14][15][16][17][18]. Furthermore, several series of pyrazoline derivatives displayed carbonic anhydrase (CA, EC 4.2.1.1) inhibitory activity [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate nHBD (0 to 4) and nHBA (3.7 to 7.2) values of all compounds within the limits (0 to 6 and 2 to 20, respectively) also supported the outcomes of the molecular docking study. Solvent accessible surface area (SASA) is defined as the accessibility of the residue to the solvent; either it is between lipid or water accessibility and it is also essential to BBB permeability [42]. The SASA values of all compounds were in an optimal range of the specified values (300 to 1000).…”
Section: Resultsmentioning
confidence: 99%